Gastrointestinal complaints in patients with osteogenesis imperfecta: The bright side of a rare genetic disorder - Sharma, Disha; Viana Rodriguez, Gracia M.; Lai, Chunwei Walter; Asif, Bilal; Talvacchio, Sara; Yang, Alexander H.; Vittal, Anusha; Derkyi, Alberta; Koh, Christopher; Wright, Elizabeth C.; Marini, Joan C.; Heller, Theo (Bone (New York, N.Y.), 2025)
Osteogenesis imperfecta (OI) is a rare hereditary disorder of connective tissue. A Danish national registry study surprisingly identified digestive causes as one of the leading causes of OI mortality. However, there is a dearth of prospective data describing gastrointestinal symptoms in OI. Our aim was to assess common gastrointestinal symptoms in an OI patient population and compare it to the general U.S. population. OI patients enrolled in a natural history protocol (NCT03575221) were prospectively evaluated for gastrointestinal symptoms and provided with PROMIS questionnaires for six gastrointestinal symptoms. The HMSS application was used to obtain T scores, score of 50 (and standard deviation of 10) representing the average of the general U.S. population. 41 OI patients were included. Median age 28 years (IQR 18–26), median BMI 28 kg/m2 (IQR 21–34), and 54 % female. OI type IV 61 %, OI type III 20 %, and remaining patients had OI type VI, VII, XIV. The mean T score for the six gastrointestinal symptoms ranged from 46 to 49, within 1 SD from the general U.S. population. Subgroup analyses showed no differences based on age, mobility, BMI, type of OI and genetic mutations (COL1A1 vs COL1A2), except increased abdominal pain with age. Patients with severe scoliosis (>50°) reported increased nausea and vomiting, and diarrhea compared to patients with mild to moderate scoliosis. We report the largest cohort of OI patients evaluated prospectively and directly for gastrointestinal complaints. Study patients, which excluded type I OI, did not report gastrointestinal symptoms higher than the general population except for abdominal pain in older patients. OI patients should be carefully evaluated in the same way as any other patient presenting with gastrointestinal complaints. •Single center, prospective study evaluating GI symptoms in OI patients.•OI patients report no more GI symptoms than the general U.S. population.•Subgroup analysis: More abdominal pain with age.•Subgroup analyses: More nausea/vomiting and diarrhea with severe scoliosis.•Subgroup analyses: No difference based on mobility, BMI, OI type, and genetic mutations.